2021
DOI: 10.1242/jeb.242665
|View full text |Cite
|
Sign up to set email alerts
|

Expression of insulin-like growth factors depends on both mass and resource availability in female green anoles (Anolis carolinensis)

Abstract: The insulin and insulin-like signaling (IIS) network is an important mediator of cellular growth and metabolism in animals, and is sensitive to environmental conditions such as temperature and resource availability. The two main hormones of the IIS network, insulin-like growth factor 1 (IGF1) and insulin-like growth factor 2 (IGF2), are present in all vertebrates, yet little is known regarding the responsiveness of IGF2 in particular to external stimuli in non-mammalian animals. We manipulated diet (low quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…The liver was chosen as the target tissue because estrogen and testosterone metabolize in the organ while gonads were too small. Furthermore, the liver was also chosen as it had a higher expression of IGF1 and IGF2 than other tissues in several reptiles ( Reding et al, 2016 ; Duncan et al, 2020 ; Marks et al, 2021 ), and differences in the expression of IGF1R/IGF2R in the liver were found between fast versus slow-growing sexually dimorphic snake ( Reding et al, 2016 ). After dissection, the liver samples were quickly cut into small pieces and stored in RNA later (Sigma-Aldrich Inc., Missouri, United States) at −20°C until used for RNA extraction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The liver was chosen as the target tissue because estrogen and testosterone metabolize in the organ while gonads were too small. Furthermore, the liver was also chosen as it had a higher expression of IGF1 and IGF2 than other tissues in several reptiles ( Reding et al, 2016 ; Duncan et al, 2020 ; Marks et al, 2021 ), and differences in the expression of IGF1R/IGF2R in the liver were found between fast versus slow-growing sexually dimorphic snake ( Reding et al, 2016 ). After dissection, the liver samples were quickly cut into small pieces and stored in RNA later (Sigma-Aldrich Inc., Missouri, United States) at −20°C until used for RNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…We selected four reference genes based on previous experimental work. Glyceraldehyde 3-phosphate dehydrogenase ( GAPDH ) has been used in mammals and reptiles ( Coulson et al, 2008 ; Sanger et al, 2014 ) with limits under caloric restrictions ( Gong et al, 2016 ; Marks et al, 2021 ). The 18S ribosomal RNA genes ( 18S ) had a primer pair already validated previously in reptiles ( Plot et al, 2012 ; Rollings et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the emphasis placed on homology with regard to ILS, it is noteworthy that our understanding of various functional aspects of IGF signaling (and IGFBPs in particular) is derived primarily from work on humans, mice or rats, despite important interspecific variation in the action of key components of ILS. For example, IGF-2 is both paternally imprinted and not produced post-natally in mice (Carter et al, 2002); however, the IGF2 gene is not only expressed in adult reptiles without imprinting (Schwartz and Bronikowski, 2016), but in green anole females it is also expressed at higher levels in calorie-restricted animals compared with controls (Marks et al, 2021). The implications for performance are currently unknown, and we still have much to learn about the action of these important signaling molecules that might affect investment in growth and reproduction versus survival in different species.…”
Section: Ils and Mtormentioning
confidence: 99%